Methylation-associated mutagenesis underlies variation in the mutation spectrum across eukaryotes - Fabián Ramos-Almodóvar; Ziyue Gao; Benjamin F. Voight; Iain Mathieson (Proceedings of the National Academy of Sciences, 2026)
Mutation spectra vary across genetic and environmental contexts, leading to differences between and within species. Most research on mutation spectrum has focused on trinucleotide (3-mer) mutation types in mammals, limiting the breadth and depth of variation surveyed. In this study, we use whole-genome resequencing data across 108 eukaryotic species—including mammals, fish, plants, and invertebrates—to characterize pentanucleotide (5-mer) noncoding mutation spectra using a Bayesian approach. Our findings reveal cytosine transition mutability at CpG sites and other sources of variation in the transition/transversion ratio as the main drivers of variation in mutation spectra across eukaryotes. We find that inferred CpG mutation rates almost perfectly predict genomic CpG depletion but are not predicted by genome-wide average CpG methylation levels. Together, our results illustrate the pivotal role of mutagenesis in shaping genome composition across eukaryotes and highlight a gap in knowledge about the mechanisms governing mutation rates.